The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/13880209.2018.1525414
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics of d-glucaro-1,4-lactone in preventing diethylnitrosamine-induced liver cancer in rats

Abstract: Context:d-Glucaro-1,4-lactone (1,4-GL) exists in many vegetables and fruits. Metabonomics has not been used to investigate the role of 1,4-GL in preventing liver cancer.Objective: The pharmacological effects and metabolite alterations of 1,4-GL on the prevention of diethylnitrosamine (DEN)-induced liver cancer were investigated.Materials and methods: Ten healthy Sprague–Dawley rats served as control and 46 were used to establish rat liver cancer model. 1HNMR-based metabonomics was used to compare the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…After febuxostat intervention, the serum AFP level showed a decreasing trend (7.937 ± 0.973). Furthermore, the serum levels of leucine, isoleucine, valine, phenylalanine, and tyrosine were determined by an established HPLC-UV method, and Fisher’s ratio was calculated ( Yang et al, 2018 ). Our results showed that Fisher’s ratio was significantly decreased in the DEN group compared with the healthy control group and significantly increased in the DEN + Febu group compared with the DEN group ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…After febuxostat intervention, the serum AFP level showed a decreasing trend (7.937 ± 0.973). Furthermore, the serum levels of leucine, isoleucine, valine, phenylalanine, and tyrosine were determined by an established HPLC-UV method, and Fisher’s ratio was calculated ( Yang et al, 2018 ). Our results showed that Fisher’s ratio was significantly decreased in the DEN group compared with the healthy control group and significantly increased in the DEN + Febu group compared with the DEN group ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…breast cancer, liver cancer) and microbial diseases (e.g. hepatitis B, tuberculosis) [ 15 , 17 , 19 , 21 , 22 , 34 , 44 , 45 ]. In 2012, Ng et al developed an untargeted metabolomics method using GC–MS to compare differences in metabolites present in fecal extractions from Cryptosporidium -positive and Cryptosporidium -negative patients [ 46 ], ultimately identifying 30 possible compounds that contributed most to the differences between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…45 Decreased serum BCAA/AAA ratio in the serum (especially BCAA/AAA <3) promotes HE development as more AAA enters the brain, leading to production of false neurotransmitters that replace major brain neurotransmitters. [46][47][48][49][50] Another reason for HE development with decreased BCAA levels is that skeletal muscles use BCAAs as energy sources to resynthesize glutamine that facilitates ammonia removal. 48 Therefore, oral BCAA supplementation can favor glutamine production in skeletal muscles, leading to ammonia removal and improvement in HE.…”
Section: Nonabsorbable Antibioticsmentioning
confidence: 99%